Current Anticoagulation Recommendation for COVID-19 Patients - Indra Prasetya (Heart Science Journal, 2021)
Thromboembolic events in COVID-19 patients can be one of the factors that aggravate the disease and increase mortality. When severe hypoxemia and hypotension occur in COVID-19 patients, the possibility of embolism should be considered. As a result, anticoagulant therapy in COVID-19 patients has an essential role in lowering disease severity and mortality. Many studies report that giving anticoagulants to COVID-19 patients can reduce mortality. Therefore, it is important to understand the role and use of anticoagulant therapy in cases of COVID-19. Several guidelines that have been issued by several health organizations in the world and Indonesia can be used as guidelines for clinicians to start anticoagulant therapy in cases of COVID-19. Various anticoagulant drug regimens have also been recommended to be used both as prophylaxis and as therapy for thromboembolism that can occur after COVID-19 cases.